When Two Worlds Collide: Creatively Reassessing the Concept of a House Beyond the Human. (June 2022) - Cole, David R.; Baghi, Yeganeh
This article reassesses the concept of a house from a non-human perspective. The two worlds that collide in this article are philosophical analyses that are "beyond the human" and sustainable engineering house design. By analyzing the houses of ten animal species for shelter/skin properties, life pedagogy (how to live), materials and resources, thermal dynamics, and structural elements, we speculate on the future of housing. The premise of this article is that "beyond the human" philosophy opens a new visage to comprehend and conceptualize what a house could be. Beyond the human theorizing is defined by philosophy that has gone beyond framing an exploration internally to the benefit of themselves, as human subject(s). This article speculates that considering animal house construction is a way forward for thought in a changing climate.